2018
DOI: 10.24294/nrcr.v1i4.212
|View full text |Cite
|
Sign up to set email alerts
|

An approach to the model for conservation of Central Mexico native grapevines

Abstract: Several and diverse native populations of wild grapevines have been reported growing in the States of Puebla, Mexico and Morelos, Central Mexico. After collection, successfully rooted vines were planted in Zumpahuacán, State of Mexico, and since 2013, their fruit were analyzed, mainly in relation to berry-weight and sweetness. Recently, the seed oil content was analyzed. Most berries harvested in 2013, 2014 and 2015 weighted less than 1 g and only berries of accession Puebla-41 (P-41) weighted nearly 2.5 g. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The devastation of forests and jungles has diminished the population of V. tiliifolia. Speci c information, on the geographical distribution and dispersion of V. tiliifolia is scarce (Sabás-Chavez et al, 2018;Franco-Mora et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The devastation of forests and jungles has diminished the population of V. tiliifolia. Speci c information, on the geographical distribution and dispersion of V. tiliifolia is scarce (Sabás-Chavez et al, 2018;Franco-Mora et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies have shown that wild germplasm from Mexico is a valuable resource for resistance to Pierce's disease, and a wide range of nematodes (Riaz et al 2018b;Riaz et al 2007;Xu et al 2008). Changes in land use, the expansion of urban areas, animal grazing, altered water rights and uses have led to deforestation, and great reductions in natural habitat and erosion of genetic diversity (Sabás-Chavez et al 2018). The Vitis species of Mexico represent a diverse and inadequately studied germplasm resource, whose conservation is important for grape breeding, cultural heritage studies and understanding of their role in the ecosystem.…”
Section: Introductionmentioning
confidence: 99%